Co- and terpolymerization of ethylene, propylene, and higher α-olefins with high propylene contents using metallocene catalysts - Villar, Marcelo Armando (2001)
The copolymerization of propylene/ethylene and terpolymerization of propylene/ethylene/α‐olefins using long‐chain α‐olefins such as 1‐octene and 1‐decene have been carried out using EtInd2ZrCl2//methylaluminoxane. High concentrations of propylene and low concentrations of α‐olefins (near 2 mol % of the total olefin concentration in the liquid phase) were used. The effect of the ethylene concentration in copolymerizations of propylene/α‐olefins was studied at medium ethylene contents (12 and 40 mol % in the gas phase). The polymers were molecularly characterized by gel permeation chromatography‐multiangle laser light scattering, wide‐angle X‐ray scattering, Fourier transform infrared spectroscopy, and DSC analyses. The shorter α‐olefin studied (1‐octene) produced the highest improvement of activity in terpolymerization at 12 mol % ethylene in the gas phase. About 2 mol % of 1‐octene in the liquid phase increases the activity and decreases the molecular weight of terpolymers with respect to corresponding copolymers, whereas the mp is increased by almost 30 °C. The “termonomer effect” is less evident when higher amounts of ethylene are used.